Operationalising the water-energy-food nexus through the theory of change. (October 2021) - Naidoo, Dhesigen; Nhamo, Luxon; Mpandeli, Sylvester; Sobratee, Nafisa; Senzanje, Aidan; Liphadzi, Stanley; Slotow, Rob; Jacobson, Michael; Modi, Albert T.; Mabhaudhi, Tafadzwanashe
Abstract: The water-energy-food (WEF) nexus facilitates understanding of the intricate and dynamic interlinkages among the three resources. Its implementation can enhance resource securities and sustainable development. Despite its potential, full adoption of the approach has been hindered by a lack of actionable strategies to guide its practical application. This is attributed to (i) poor data (ii) lack of empirical evidence, (iii) inadequate analytical tools, and (iv) lack of clarity on applicable spatial scale. This study undertook a literature review, coupled with systemic analyses of a WEF nexus analytical model, whose outputs were used as a basis to develop a Theory of Change, an iterative outline for operationalising the approach in the context of southern Africa. The consultative and iterative Theory of Change culminated with the formulation of pathways to (i) overcome the barriers impeding WEF nexus operationalisation, (ii) mitigation of trade-offs while enhancing synergies towards attaining simultaneous resource securities, (iii) poverty alleviation and reduction of inequalities, and (iv) reconciling policy with implementation scale. The WEF nexus operationalisation outcomes are linked to Sustainable Development Goals 2 (zero hunger), 6 (clean water and sanitation), and 7 (affordable and clean energy), with synergies to SDGs 1 (no poverty), 5 (gender equality), 8 (decent work and economic growth), 12 (responsible consumption and production), 13 (climate action), 14 (life below water), and 15 (life on land). Operationalising the WEF nexus through an interactive process can inform sustainable pathways towards resource security, job and wealth creation, improved livelihoods and well-being, and regional integration. Highlights: Informed WEF nexus operationalisation provides strategic pathways towards sustainable development. Stakeholder consultation culminated in a programmatic Theory of Change to operationalise the WEF nexus. The Theory of Change facilitated WEF nexus transition from theory to practice. Operationalising the WEF nexus assists in solving complex sustainability challenges.